Compressibilty characteristics of fibrous peat soil - Yulindasari, Yulindasari (2006)
Peat has been identified as one of major groups of soils found in Malaysia. Peat deposit covers large area of West Johore especially Pontian, Batu Pahat, and Muar. Despite of this fact, not much research has been focused on the compression behavior of peat. This study is focused on the compressibility characteristics of fibrous peat based on time-compression curves derived from consolidation tests. The peat samples were collected from Kampung Bahru, Pontian, West Johore by block sampling method. The laboratory testing program included the standard laboratory testing for identification and classification purposes, i.e., Scanning Electron Micrograph (SEM), shear box test, constant head permeability test, Oedometer tests, and large strain consolidation test using Rowe cell. The results of the study show that the peat soil can be classified as fibrous peat with low to medium degree of decomposition (H4 in von Post scale) and of very high organic content (97 %) and fiber content (90 %). The natural water content of the peat is 608 % which corresponds to initial void ratio of about 9. The undrained shear strength of peat is 10.10 kPa, with sensitivity of 5.64. The initial permeability is high, but it decreases significantly with applied pressures. The fibrous peat has a high compressibility with significant secondary compression stage, which is not constant with the logarithmic of time. Eventhough the duration of the primary consolidation was short, but the settlement was high. This is due to high initial void ratio. Besides, the magnitude of the secondary compression of fibrous peat is also significant with respect to the design life of a structure. The comparison between the results of the consolidation test using Rowe and Oedometer cells show that the use of Rowe cell for the evaluation of the consolidation characteristics of soil exhibiting secondary compression is advantageous because it enables the observation of the large deformation. The compression index (cc) obtained from consolidation test on Rowe cell was 3.128, while the coefficient of secondary compression (ca) range from 0.102 to 0.304. The settlement analysis performed for the hypothetical case of an embankment on peat deposit showed that the compression of fibrous peat deposit can be estimated based on the time-compression and the time-excess pore water pressure curves.